Fecal carriage of Escherichia coli and Klebsiella spp. as major reservoirs of clinically important resistance markers - Razaghi, Maryam; Torabi, Parisa; Nazemalhosseini Mojarad, Ehsan; Tajeddin, Elahe; Jahani Sherafat, Somayeh; Rashidan, Marjan; Sadat Seyedjavadi, Sima; Alebouyeh, Masoud; Zali, Mohammad Reza (Archives of Advances in Biosciences, 2012)
Intestinal normal flora can become reservoirs of antibiotic resistance genes present among the strains responsible for nosocomial infections. It is suggested that gram negative intestinal bacterial flora have increased capacities to obtain antibiotic resistance genes and therefore can act as main reservoirs for transfer of resistance genes to other pathogenic bacteria. This study aimed to compare fecal carriage of clinically important resistance markers for more frequent members of enterobacteriacae between nondiarrheal and community associated diarrheal patients (control group) versus their counterparts from the patients with nosocomial infections (case group). 261 stool and 190 clinical samples were collected from outpatient and hospitalized patients from 6 hospitals in Tehran, Iran. The samples were cultured on MacConkey agar plates and colonies were identified by standard biochemical methods. Antibiotic sensitivity testing of the isolates against 13 antibiotics was performed according to the CLSI guideline using the disk diffusion method. Among stool and clinical samples, more frequent identified enterobacteriaceae bacteria were included E. coli (58.99/ 3.15%), Klebsiella spp. (22.61/7.36%), and other members of enterobacteriaceae (8.86/1.06%), respectively. Overall, resistance against four of the main antibiotics (3th and 4th generation cephalosporins, gentamicin, imipenem, and ciprofloxacin) was significantly higher among the case group (50-75% versus 10-14%). Analysis of these results showed similar dissemination of resistance phenotypes among the isolates from the control group in ranges of 1.5-7.6% and 4.4% for E. coli and Klebsiella spp., respectively. Our results suggested that the fecal carriage of resistant phenotypes related to the β-lactam antibiotics in E. coli and Klebsiella spp. in compare to the clinical isolates is rapidly increasing. This may be caused by dissemination of β-lactamase producing E. coli in the community from the hospitals. There were no significant correlations between the two groups of the samples, as the clinical samples had shown 3 to 7 folds excess resistance phenotypes. Surveillance studies of the resistance patterns among the samples from different regions will provide awareness about dissemination of these bacteria within the community as reservoirs of main resistance markers.